2021
DOI: 10.3389/fonc.2021.777867
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 as a Rational Target for Intervention in CDK4/6 Inhibitor Resistant, Hormone Receptor Positive Breast Cancer

Abstract: With the adoption of inhibitors of cyclin dependent kinases 4 and 6 (CDK4/6i) in combination with endocrine therapy as standard of care for the treatment of advanced and metastatic estrogen receptor positive (ER+) breast cancer, the search is now on for novel therapeutic options to manage the disease after the inevitable development of resistance to CDK4/6i. In this review we will consider the integral role that the p53/MDM2 axis plays in the interactions between CDK4/6, ERα, and inhibitors of these molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…2 A, B, Table 1 ). Moreover, although CDK4 and MDM2 have been demonstrated to be involved in lung cancer, their roles as therapeutic targets have not yet been firmly established [ 30 ]. Regardless, they were ranked the most prominent in this assessment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A, B, Table 1 ). Moreover, although CDK4 and MDM2 have been demonstrated to be involved in lung cancer, their roles as therapeutic targets have not yet been firmly established [ 30 ]. Regardless, they were ranked the most prominent in this assessment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Translating our findings from WGS and ChIP-seq analyses for clinical applications requires prospective trials. By applying our method, we identified a preponderance of probable driver genes, some of which are currently under clinical investigation [ 30 , 56 59 ]. This approach offers significant benefits for patient selection and potentially improves the efficacy of clinical trials by targeting individuals with relevant genetic profile.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 overexpression leads to interruption of cell senescence and hence CDK4/6is resistance. For this reason, MDM2 inhibitors may be useful in treating patients' resistant to CDK4/6is, despite further studies being needed [39].…”
Section: Mdm2 Overexpressionmentioning
confidence: 99%
“…[90][91][92] Role of SIPL1/SHARPIN in BC oncogenesis, especially ER+ BC, has not been thoroughly studied until recent years. It has been reported that overexpression of SIPL1/SHARPIN in BC cells reduces p53 protein levels and p53 target genes MDM2, 93 P21, P53INP1, and BTG2, and increases activity of MAPK and AMPK pathways, 94,95 leading to resistance to TAM through AKT activation and NF-kB signaling pathways. 96,97 Various oncogenic miRNAs regulated by estrogen/ERα interaction signaling have been found to cause endocrine drug resistance during treatments.…”
Section: Other Er-mediated Endocrine Therapy Resistance Pathwaysmentioning
confidence: 99%